Smart bites: low-cost and educational recipes for Fort Collins families - Phillips, Katherine, author (Colorado State University. Libraries, 2024)
I wrote this cookbook to provide easy, healthy, and low-cost meals for Fort Collins families. I also wrote this cookbook to help educate families in Fort Collins about nutrition and economics. With the increased cost of living, I wanted to help local families cook meals for cheaper. Food is a large part of people's budget, and food prices have increased dramatically recently. There are many cookbooks out there for quick, healthy, and cheap meals, but none that I know of that are also educational. I tried to keep it short by adding a paragraph or two to each recipe. This way, people can learn while not having to read a whole academic paper. I want this cookbook to be accessible, useful, and interesting.
Department of Economics at Colorado State University. Honors Program.
Keywords: economics; Fort Collins; cookbook; recipes; healthy; nutritious; Colorado